Microbial growth in drinking-water supplies : problems, causes, control and research needs - Kooij, D. van der, 1946-; Wielen, Paul W. J. J. van der (IWA Publishing, 2014)
Maintaining the microbial quality in distribution systems and connected installations remains a challenge for the water supply companies all over the world, despite many years of research. This book identifies the main concerns and knowledge gaps related to regrowth and stimulates cooperation in future research. Microbial Growth in Drinking Water Supplies provides an overview of the regrowth issue in different countries and the water quality problems related to regrowth. The book assesses the causes of regrowth in drinking water and the prevention of regrowth by water treatment and distribution. Editors: Dirk van der Kooij and Paul W.J.J. van der Wielen, KWR Watercycle Research Institute, The Netherlands.